2000
DOI: 10.1128/aem.66.7.3098-3101.2000
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a Putative Mannose-Specific Phosphotransferase System Enzyme IIAB Component in a Leucocin A-Resistant Strain of Listeria monocytogenes , as Shown by Two-Dimensional Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis

Abstract: Leucocin A is a class IIa bacteriocin produced by Leuconostoc spp. that has previously been shown to inhibit the growth of Listeria monocytogenes. A spontaneous resistant mutant of L. monocytogenes was isolated and found to be resistant to leucocin A at levels in excess of 2 mg/ml. The mutant showed no significant cross-resistance to nontype IIa bacteriocins including nisaplin and ESF1-7GR. However, there were no inhibition zones found on a lawn of the mutant when challenged with an extract containing 51,200 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 40 publications
1
102
0
Order By: Relevance
“…For example, the EIIAB component of a mannose class PTS (called Mpt) was found to be absent from several spontaneous leucocin A-resistant L. monocytogenes mutants (693), while overproduction of a ␀-glucoside-specific PTS in the same organism led to pediocin PA-1 resistance (294). The role of the Mpt PTS in class IIa bacteriocin resistance has been studied in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the EIIAB component of a mannose class PTS (called Mpt) was found to be absent from several spontaneous leucocin A-resistant L. monocytogenes mutants (693), while overproduction of a ␀-glucoside-specific PTS in the same organism led to pediocin PA-1 resistance (294). The role of the Mpt PTS in class IIa bacteriocin resistance has been studied in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…In Listeria species, low-level resistance (two-to fourfold) to class IIa bacteriocins is caused by alterations in membrane lipid composition (13,49,50). High-level resistance (1,000-fold) in Listeria monocytogenes and Enterococcus faecalis results primarily from the loss of EII t Man , which is encoded by the mpt (mannose permease two) operon (14,26,38). Highlevel resistance in L. monocytogenes is also caused by the loss of 54 factor (encoded by rpoN) (43) and the 54 -associated activator ManR (14), which together positively regulate the mpt operon.…”
mentioning
confidence: 99%
“…Initially, these peptides are thought to bind to negatively charged molecules, such as teichoic acids in the cell wall (7). Subsequently, they transfer to the cytoplasmic membrane, where they interact with anionic phospholipids (9) and a phosphoenolpyruvate-dependent phosphotransferase system (PTS) permease of the mannose structural family (EII t Man ) (38). Once they are bound to cell membranes, class IIa bacteriocins fold into a ␀␣ conformation (19,48,51) in which the nonpolar ␣-helical region is inserted into the phospholipid bilayer (32).…”
mentioning
confidence: 99%
“…The expression of this gene was highly suppressed after incubation for 240 h at 4 °C, and the treatment with nisin resulted in lower dltA expression as compared with the peptide P34. Previous studies have shown that a 1000-fold increased resistance to class IIa bacteriocins in L. monocytogenes and Enterococcus faecalis resulted from the loss of mptA expression [38,42,43]. The cell wall of L. monocytogenes is composed by a thick peptidoglycan layer containing two types of anionic polymers: teichoic acids (TA), which are covalently linked to the peptidoglycan, and lipoteichoic acids (LTAs), which are poly phosphoglycerols substituted with a Dalanyl ester or a glycosyl residue and anchored in the membrane by their glycolipid moiety [44].…”
Section: Resultsmentioning
confidence: 99%